A practical guide to item bank calibration with multiple matrix sampling - Güneş Ertaş; Serkan Arıkan; Eren Can Aybek (International Journal of Assessment Tools in Education)
When it is required to estimate item parameters of a large item bank, Multiple Matrix Sampling (MMS) design provides an efficient way while minimizing the test burden on students. The current study exemplifies how to calibrate a large item pool using MMS design for various purposes, such as developing a CAT administration. The purpose of the current study is to explain and provide an example of how to use MMS design for item bank calibration. Two functions of mirt package, mirt() and multipleGroup() were compared using real data. The results of the present study showed that the standard mirt() function is more practical and makes more precise estimations compared to the multipleGroup() function.